Evaluation of mineral nutrient contents in plants of 'Valência' orange submitted to fertigation - Ragozo, Carlos Renato Alves; Büll, Leonardo Theodoro [UNESP]; Bôas, Roberto Lyra Villas [UNESP]; Duenhas, Luiza Helena (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2009)
This work aimed to compare fertigation to conventional fertilization in a five-year-old 'Valência' orange orchard, irrigated by microsprinklers. The conventional fertilization, using the recommended dosage for the crop, was parceled out in three during the year. In the fertigation treatments a complete dose, 1/2 and 1/3 of the conventional fertilization dose, parceled out in ten in a year, were used. Trunk circumference and leaf volume, leaf chlorophyll content and fruit yield and quality were measured. For the first year, significant differences among the treatments for the evaluated parameters were not observed; however, it was noticed that fertigation treatments caused less nutritional unbalance, obtained by DRIS. The fertigation treatment using half dosage showed the best result regarding to fruit yield and quality.
Avaliação dos teores nutricionais em laranjeira 'Valência', sob fertirrigação
Keywords: Citrus sinensis range; DRIS; Fertigation